Connecting museums - O'Neill, Mark, 1956-; Hooper, Glenn, 1963- (London ; New York, NY : Routledge/Taylor & Francis Group, 2020)
"Connecting Museums explores the boundaries of museums and how external relationships are affected by internal commitments, structures and traditions. Focusing on museums' relationship with heath, inclusion, and community, the book provides a detailed assessment of the alliances between museums and other stakeholders in recent years. With contributions from practitioners and established and early-career academics, this volume explore the ideas and practices through which museums are seeking to move beyond what might be called one-off contributions to society, to reach places where the museum is dynamic and facilitates self-generation and renewal, where it can become not just a provider of a cultural service, but an active participant in the rehabilitation of social trust and democratic participation. The contributors to this volume provide conceptual critiques and clarification of a number of key ideas which form the basis of the ethics of museum legitimacy, as well as a number of reports from the front line about the experience of trying to renew museums as more valuable and more relevant institutions. Providing internal and external perspectives, Connecting Museums presents a mix of applied and theoretical understandings of the changing roles of museums today. As such, the book should be of interest to academics, researchers and students working in the broad fields of museum and heritage studies, material culture, and arts and museum management"--
A social museum by design / Mike Benson and Kathy Cremin -- Notes from the frontline : partnerships in museums / Bernadette Lynch -- The social role of museums : from social inclusion to health and wellbeing / Nuala Morse -- Amgueddfa Cymru-National Museum Wales and the journey towards cultural democracy / Janice Lane and Nia Williams -- Breaking out of the museum core : conservation as participatory ontology and systemic action inquiry / Helen Graham -- Thinking through museums and health in Glasgow / Mark O'Neill, Pete Seaman and Duncan Dornan -- Partnership for health : the role of cultural and national assets in public health / Helen Chatterjee -- Transforming health, museums and the civic imagination / Esme Ward -- "Who me?" : the individual experience in participative and collaborative projects / Mike Tooby -- Coalville heroes / Graham Black and Stuart Warburton -- On a hungry hill : museology and community on the Beara Peninsula / Glenn Hooper -- ''Only connect" : the heritage and emotional politics of show-casing the suffering migrant / Christopher Whitehead and Francesca Lanz -- The changing shape of museums in an increasingly digital world / Oonagh Murphy -- Material presence and virtual representation : the place of the museum in a globalised world / Pat Cooke -- Curating democratic and civic engagement / Anwar Tlili.
OCLC-licensed vendor bibliographic record.
Keywords: Museums and community; Museums -- Social aspects; Museums -- Management; LANGUAGE ARTS & DISCIPLINES / Library & Information Science; SOCIAL SCIENCE / Archaeology